РАЗРАБОТКА ТЕХНОЛОГИИ УТИЛИЗАЦИИ ДИСТИЛЛЕРНОЙ ЖИДКОСТИ КУНГРАДСКОГО СОДОВОГО ЗАВОДА СУЛЬФАТСОДЕРЖАЩИМИ СОЛЯМИ КАРАКАЛПАКСТАНА - Реймов, К.Д.; Артиков, М.Б.; Базарбаева, Л.Г. (SCIENCE and SOCIETY, 2024)
Following optimum technological parametres the are established clearing by Karaumbetsky rapa and mirabilit the Tumrjuksky deposit of distilar liquids-a manufacture withdrawal carbonatium soda «Kungradsky soda factory»: norm of sulphatic salts-100 % on concerning the calcium maintenance, during of process - 1,5-2 hours and temperature of process no more 60ºС.The basic technological scheme is developed the process consisting of a stage of preparation sulfat of a solution and three steps of clearing distilar of a liquid.
Keywords: ammonia; natural soda; nepheline; sodium; hydrohide; ammonia method; distillation; processing; gypsum; chalk; technological cycle; filter; suspension; solution preparation; Caraumbet brine; insoluble calcium sulfate; hypsomagnesium; stoichiometry